Large axillary accessory breast hamartoma: a rare entity - Premi, Vimugdha; Arora, Manali; Syed, Anjum; Gupta, Priyanka; Sharda, Prateek; Ravi, Bina (International Journal of Research in Medical Sciences, 2019)
Hamartomas are uncommon benign tumours of axilla and breast. They show varied imaging appearances depending upon the proportion of various tissue elements present. The mammographic, ultrasound and elastographic appearances of a case of left axillary hamartoma is described in a 49 years old Indian patient. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-IN X-NONE HI <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>